Urinary protein components. I. Basis and general methodology (Revista Española de Fisiología, 1971)
Protein clearances of blood components is becoming one of the most accured pro cedures to test glomerule and tube behaviour. Molecular protein components lighter than 150,000 M.W. usually, are cleared.A three points scale ranging from 60 to 900,000 M.W. is explored. Quantitative immuno-diffusion and electroforesis are used. Net clearance and sieving coefficient are, among others, the main patterns to be determined.